Disain Mitigasi Risiko Penularan Covid-19 di Lingkungan Industri Padat Karya dengan Metode FMEA - Sugeng Santoso; Septian Sugestyo Putro; Ari Ana Fatmawati; Caesarani Gloria Putri; Sa’dillah Sa’dillah (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
Indonesia has confirmed its first case of Covid-19 transmission on March 2, 2020 and since then the transmission of the virus has become more widespread and has created new epicenters. The epicenter always involves a crowd, including in labor-intensive factory areas. This research method uses quantitative-descriptive. Companies that operating labor-intensive require the involvement of large numbers of people. In the production process, the distance between workers is not far apart, thus increasing the risk of virus transmission. The latest case in September 2020, 150 employees of a factory in the city of Purbalingga tested positive for the Covid-19 virus. It is strongly suspected that transmission occurs in the work area through asymptomatic labor. With the continued occurrence of Covid-19 transmission in industrial areas, this article aims to submit a proposal for the application of a risk mitigation design for the risk of Covid-19 transmission in labor-intensive industries using the FMEA method, which includes the layout of the work area, the flow of human movement in the factory area, and the application of health protocols in the hope of helping labor-intensive industries in suppressing and preventing the transmission of Covid-19